ASP.NET Core 5 Secure Coding Cookbook - Canlas, Roman; Price, Ed (Packt Publishing, 2021)
Learn how to secure your ASP.NET Core web app through robust and secure code Key Features Discover the different types of security weaknesses in ASP.NET Core web applications and learn how to fix them Understand what code makes an ASP.NET Core web app unsafe Build your secure coding knowledge by following straightforward recipes Book Description ASP.NET Core developers are often presented with security test results showing the vulnerabilities found in their web apps. While the report may provide some high-level fix suggestions, it does not specify the exact steps that you need to take to resolve or fix weaknesses discovered by these tests. In ASP.NET Secure Coding Cookbook, you'll start by learning the fundamental concepts of secure coding and then gradually progress to identifying common web app vulnerabilities in code. As you progress, you'll cover recipes for fixing security misconfigurations in ASP.NET Core web apps. The book further demonstrates how you can resolve different types of Cross-Site Scripting. A dedicated section also takes you through fixing miscellaneous vulnerabilities that are no longer in the OWASP Top 10 list. This book features a recipe-style format, with each recipe containing sample unsecure code that presents the problem and corresponding solutions to eliminate the security bug. You'll be able to follow along with each step of the exercise and use the accompanying sample ASP.NET Core solution to practice writing secure code. By the end of this book, you'll be able to identify unsecure code causing different security flaws in ASP.NET Core web apps and you'll have gained hands-on experience in removing vulnerabilities and security defects from your code. What you will learn Understand techniques for squashing an ASP.NET Core web app security bug Discover different types of injection attacks and understand how you can prevent this vulnerability from being exploited Fix security issues in code relating to broken authentication and authorization Eliminate the risks of sensitive data exposure by getting up to speed with numerous protection techniques Prevent security misconfiguration by enabling ASP.NET Core web application security features Explore other ASP.NET web application vulnerabilities and secure coding best practices Who this book is for This ASP.NET Core book is for intermediate-level ASP.NET Core web developers and software engineers who use the framework to develop web applications and are looking to focus on ...